Synthesis novel flavone from vanillin - Rahmawati, R; Sofia , Baiq Fara Dwirani (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2023)
Flavone compounds present as secondary metabolites in many plants have beneficial phytochemical activity. Isolation of flavones from various parts of plants has been widely carried out, but the synthesis pathway is another way to obtain higher yields. This research aimed to synthesize flavone compounds from vanillin and 2-hydroxyacetophenone through chalcone intermediates to produce a 74% yield using an iodide catalyst. This new flavone compound has been used as a chemosensor to detect anions